In vitro ASSESSMENT OF PHARMACOLOGICAL ACTIVITIES OFJacaranda mimosifolia Mart. SEED EXTRACT AND in silico APPROACHESFOR PROTEIN ANALYSIS (Applied Biological Research, 2024)
The genus Jacaranda is a significant representative of the tribe Tecomeae in the family Bignoniaceae, which comprises indigenous species from the region of South America that are present across tropical areas all over the globe. The primary goal of the present study deals with conducting phytochemical screening in addition to evaluating the effective antioxidant, anti-inflammatory and antimicrobial actions of Jacaranda mimosifolia crude extract. The investigation revealed the presence of chemicals like glycosides, carbohydrates, tannins, proteins, amino acids, terpenoids, fats and oils. ABTS and DPPH scavenging tests were employed to investigate the antioxidant action of the methanolic extract and the IC50 values are 144.231 M/µL and 12.957 M/µL respectively. It showed effective antimicrobial action against P. aeruginosa, S. typhi, S. mutans and E. coli in four different concentrations. In addition, the extract was assessed for anti-inflammatory efficacy utilising the Bovine Serum Albumin Denaturation Assay and the IC50 value was 213.85 M/µL. Moreover, the structural and physiochemical features of the protein, ribosomal protein L23, present in Jacaranda mimosifolia which exhibit antioxidant actions was characterized via various bioinformatics tools. According to the findings, it is evident that extracts of its seed could be a viable substitute for synthetic antioxidant, antimicrobial, and anti-inflammatory drugs.
Keywords: Anti-inflammatory; antimicrobial; in silico analysis; Jacaranda mimosifolia; phytochemicals